Intensification of Midwestern Agriculture as a Regional Climate Modifier and Atmospheric Boundary Layer Moisture Source. Issue 6 (2nd November 2019) - Hill, Andrew C.; Mitchell, Martin; Yuan, Fei; Ruhland, Christopher T.
Abstract : Agricultural land use changes have likely played an important role in modifying local and regional climate factors. According to a recent study, summers in the Midwest were significantly cooler and wetter due to the dramatic increases in production of corn and soybeans caused by an intensification of agricultural practices (Alter et al. 2018 ). In this context, this study examines regional changes manifested in multiple climate variables and directly quantifies the magnitude of potential moisture contributions from Midwest corn and soybean agriculture. Meteorological data were collected for daily minimum, maximum, and dewpoint temperatures over a sixty-one-year study period from fifty-nine National Weather Service first-order stations and cooperative network stations. Regional growing season climatology for two study regions that focused on the rain-fed Midwest Corn Belt and the southern United States extending to the Gulf Coast was analyzed. Further, vapor pressure deficit was calculated to ascertain any regional changes. Field surveys of corn and soybean crop transpiration were used in a multivariate model to estimate lower atmospheric moisture contributions at midday during peak season directly from intensified rain-fed agriculture. Findings indicate an increase in regional dewpoint, associated with elevated nocturnal minimums and suppression of both daily maximum and vapor pressure deficit, concentrated in the Midwest Corn Belt, which was not evident within the South. The estimation results of the atmospheric moisture contributions from the Corn Belt confirm the intensification of Midwestern agriculture as a regional climate modifier. Key Words: agriculture, dewpoint, energy balance, humidity, regional climate.